Understanding Social Accountability: Politics, Power and Building New Social Contracts - and Hickey, Sam; King, Sophie (The Journal of Development Studies, 2016)
Calls to deepen levels of social accountability within social protection interventions need to be informed by the now extensive experience of promoting social accountability in developing countries. Drawing on a systematic review of over 90 social accountability interventions, including some involving social protection, this paper shows that politics and context are critical to shaping their success. We argue that the politics of social protection and of social accountability resonate strongly with the broader project of transforming state-society relations in developing countries. This requires a reconceptualisation of social accountability and social protection in terms of the broader development of ‘social contracts’, and that the current emphasis on promoting bottom-up forms of accountability needs to be balanced by efforts to strengthen and legitimise public authority in developing countries.